2020
DOI: 10.3390/ma13030597
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufactured Large Zr-Based Bulk Metallic Glass Composites with Desired Deformation Ability and Corrosion Resistance

Abstract: Zr-based bulk metallic glasses have been attracting tremendous interest of researchers because of their unique combination of mechanical and chemical properties. However, their application is limited as large-scale production is difficult due to the limitation of cooling rate. Recently, additive manufacturing technology has been proposed as a new solution for fabricating bulk metallic glasses without size limitation. In this study, selective laser melting technology was used to prepare Zr60Fe10Cu20Al10 bulk me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…It was reported that structural defects in as-cast sample representing chemical discontinuities with sharp phase boundaries to the glassy matrix were more detrimental for its corrosion resistance than pore defects in the SLM sample, which are a geometry defect [410]. In another study, the corrosion rate of SLMed Zr-based BMG (Zr 60 Fe 10 Cu 20 Al 10 ) was higher than the as-cast sample and increased with an increase in exposure time due to crystallization and lower amorphous content [402].…”
Section: Corrosion Behavior Of Powder Bed Fusion Additive Manufactured Bmgsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was reported that structural defects in as-cast sample representing chemical discontinuities with sharp phase boundaries to the glassy matrix were more detrimental for its corrosion resistance than pore defects in the SLM sample, which are a geometry defect [410]. In another study, the corrosion rate of SLMed Zr-based BMG (Zr 60 Fe 10 Cu 20 Al 10 ) was higher than the as-cast sample and increased with an increase in exposure time due to crystallization and lower amorphous content [402].…”
Section: Corrosion Behavior Of Powder Bed Fusion Additive Manufactured Bmgsmentioning
confidence: 95%
“…The first attempt to used SLM to fabricate fully amorphous BMG components under the appropriate conditions was carried out by Pauly et al [388] in 2013. Since then, several other BMGs based on Fe [388][389][390][391][392][393][394][395][396], Al [397][398][399][400], Zr [401][402][403][404][405][406][407][408][409][410][411][412][413][414], Cu [415,416], Pd [417], and Ti [418] have been fabricated using the laser PBF process. A sample made of Fe-based BMGs as large as 45 mm in diameter and 20 mm in length was fabricated by Wang et al [419].…”
Section: Bulk Metallic Glasses (Bmgs)mentioning
confidence: 99%
“…High stress can cause cracking, delamination, deformation, and fatigue failure of 3D-printed parts, especially for these amorphous alloys with inherent brittleness and low fracture toughness [91]. However, some studies have also found that cracks also appear when zirconium-based bulk metallic glasses prepared by SLM [109]. Zr 60 Fe 10 Cu 20 Al 10 BMG was prepared by selective laser melting technology, and the laser parameters used to manufacture fully dense amorphous samples can be obtained.…”
Section: Defects In Slmmentioning
confidence: 99%
“…The former is characterized by a clear chemical discontinuity with the vitreous matrix phase boundary, while the latter is a geometric discontinuity, leading to low chloride ion erosion driving, leading to the formation and diffusion of pits. Luo [109] compares amorphous and polycrystalline components of the same component. Large metallic glasses with amorphous structures usually exhibit good corrosion resistance.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…However, due to the characteristics of long-range disorders and short-range orders in homogeneous macrostructures of BMGs, a highly localized plastic deformation via shear bands usually governs mechanical properties, resulting in catastrophic room-temperature brittleness [ 1 , 2 , 3 , 4 , 5 , 6 ], severely limiting future practical applications as engineering materials. In order to overcome catastrophic fracture and improve the plastic deformability of BMGs, various approaches have been suggested [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], which are classified into three basic strategies: The first is to create structural heterogeneity by tailoring chemical compositions, cooling rates, cryogenic thermal cycling, elastic loading, and so on [ 7 , 8 ]. The second is to introduce the second crystalline phase into a glassy matrix to prepare BMG composites by heating, manipulating the solidification process, or altering chemical compositions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%